S, V-co-doped porous Ni2P material and preparation method and application thereof
The preparation of S, V-co-doped porous Ni2P materials through hydrothermal method solved the problems of catalyst corrosion, poisoning and kinetic slowness in salt water electrolysis, and achieved efficient electrochemical decomposition performance.
Patent Information
- Application Number
- CN202411662890.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The prior art has problems of catalyst corrosion, poisoning and kinetic slowness in saline electrolysis, which makes it difficult to achieve efficient seawater decomposition.
NiV-LDH precursor was prepared by hydrothermal method, and S anions were introduced during the calcination process to obtain a porous Ni2P material co-doped S, V, and used for efficient electrochemical decomposition of water.
The material exhibits excellent HER and OER catalytic activity in alkaline brine, and can achieve a current density of 10mA·cm-2 only required 1.48V, and has good stability and durability.
Smart Images

Figure CN119506959A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic water catalysts, and more specifically relates to an S, V-co-doped porous Ni2P material and a preparation method and application thereof. Background Art
[0002] Water electrolysis provides an efficient chemical pathway for producing renewable hydrogen energy. There is a severe shortage of freshwater resources globally, accounting for only 2.5% of the world's total water resources. Large-scale freshwater electrolysis will put heavy pressure on important freshwater resources. Therefore, for areas with scarce freshwater resources and drought, direct electrolysis of brackish water provides an opportunity for large-scale hydrogen production. This technology not only alleviates the pressure of scarce freshwater resources to a certain extent, but also shows great practical significance for arid areas such as those with limited freshwater resources and abundant renewable electricity. The main challenges faced by brackish water in arid areas are similar to those of seawater, which comes from the presence of a large amount of Cl in the water. - , and ClER will compete with OER. - The strong corrosiveness to the catalyst, and the magnesium and calcium ions in the brine form insoluble precipitates on the electrode surface, leading to catalyst poisoning, are not conducive to the catalytic efficiency and stability of the catalyst. In addition, the inherent low conductivity of seawater is not conducive to HER kinetics. Coupled with the inherent kinetic sluggishness of OER, it becomes more difficult to achieve efficient seawater decomposition. In addition, the complexity of the matrix also makes it difficult to study the reaction process and mechanism of seawater electrolysis. Due to the existence of the above obstacles, the development of brine electrolysis on the road to industrialization has been relatively slow.
[0003] Precious metal materials such as Pt, Ir and Ru are good catalysts for water electrolysis, but their low abundance and high cost limit their widespread application. Therefore, it is imperative to develop efficient non-precious metal catalysts as alternatives. According to literature reports, transition metal phosphides, especially Fe, Co, and Ni-based phosphides, exhibit excellent electrical conductivity and high electron density near the Fermi level, which improves the intrinsic conductivity of the material. Therefore, the material can achieve higher carrier transfer efficiency and higher catalytic activity during electrocatalysis. For metal phosphides, in the metal phosphide structure with a P-terminated surface, the polarization-induced partial negative charge located at the P center attracts protons as a basis, making it easier to discharge, thereby promoting HER. Recently, a lot of research work has been devoted to exploring LDH as a precursor to synthesize bimetallic LDH-derived metal phosphides for efficient overall water splitting. However, the electrocatalytic performance and long-term stability of metal phosphides are still far from satisfactory.
[0004] Therefore, how to provide an S, V-co-doped porous Ni2P material and its preparation method and application is a problem that technical personnel in this field need to solve urgently. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies in the prior art, the present invention provides a S, V-co-doped porous Ni2P material and its preparation method and application. The present invention utilizes the advantage of flexible and variable components of LDH, prepares NiV-LDH precursor by hydrothermal method, then introduces S anions during calcination, and finally obtains anion- and cation-co-doped S, V-Ni2P / NF.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a S, V-co-doped porous Ni2P material comprises the following steps:
[0008] (1) Weigh Ni(NO3)2·6H2O, VCl3, urea and NH4F, dissolve them in water, and stir to obtain a mixed solution;
[0009] (2) adding the nickel foam and the mixed solution into a stainless steel autoclave lined with polytetrafluoroethylene, heating to react, and then washing with water and drying to obtain a NiV-LDH precursor;
[0010] (3) NiV-LDH precursor, S powder and NaH2PO2 powder are placed in the downstream, midstream and upstream of the tube of a tube furnace, respectively, the tube furnace is heated in argon gas, then kept warm and naturally cooled to room temperature to obtain S, V-Ni2P / NF material.
[0011] Preferably, the molar ratio of Ni(NO3)2·6H2O, VCl3, urea and NH4F in step (1) is 2.85:0.15:6:4.
[0012] Preferably, the stirring time in step (1) is 30 min.
[0013] Preferably, the heating temperature in step (2) is 120° C. and the heating time is 6 hours.
[0014] Preferably, the mass ratio of the S powder to the NaH2PO2 powder in step (3) is 1:100.
[0015] Preferably, the heating rate of the tubular furnace in step (3) is 2°C / min, the temperature is raised to 350°C, and the holding time is 2h.
[0016] The present invention also provides an S, V-co-doped porous Ni2P material prepared by the above method.
[0017] The present invention also provides the use of the above-mentioned S, V-co-doped porous Ni2P material in salt water decomposition.
[0018] It can be seen from the above technical solution that, compared with the prior art, the present invention provides an S, V-co-doped porous Ni2P material and a preparation method and application thereof, which have the following beneficial effects:
[0019] (1) The present invention prepares S, V-Ni2P / NF nickel phosphide co-doped with S and V by a two-step hydrothermal-gas-solid reaction synthesis method for efficient electrochemical water decomposition. The S, V-Ni2P / NF electrode is in situ grown on nickel foam and has a special micro-flower structure, showing excellent HER and OER catalytic activity. In alkaline salt water, the S, V-Ni2P / NF electrode, which is also a bifunctional electrocatalyst, only needs 1.48V to reach 10mA·cm -2 The excellent performance of S, V-Ni2P / NF is mainly due to its special morphology and the synergistic effect of S, V co-doping. The dual doping of anions and cations optimizes the electronic structure of the catalyst, further optimizes the electronic structure and electronic arrangement of the catalyst, accelerates the charge transfer rate of the catalyst, and the porous micro-flower structure has a large electrochemically active specific surface area, which provides sufficient possibility for the exposure of more active sites, thereby improving the catalytic activity of the catalyst.
[0020] (2) V dopants have multiple redox states and an atomic radius closer to that of Ni, so they can easily induce subtle lattice distortion and redistribution of electron density in the Ni structure. In addition, the electron-deficient non-metallic S dopant with low electronegativity can effectively rearrange the electronic structure of nickel phosphide. In alkaline media, the prepared S, V-Ni2P / NF electrodes exhibit excellent oxygen and hydrogen evolution performance. S, V-Ni2P / NF only require overpotentials of 259 and 236 mV, respectively, to reach 100 mA cm -2 In alkaline salt water, only 1.48 and 1.72 V are required to reach 10 mA cm -2 and 100mA·cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0022] Figure 1 Schematic diagram of the synthesis of S, V-Ni2P / NF.
[0023] Figure 2 (a) and (b) are the XRD and SEM images of NiV-LDH, respectively.
[0024] Figure 2 (c)-(f) are characterization pictures of S, V-Ni2P / NF, including: (c) XRD picture; (d), (e) SEM pictures; (f) element distribution picture.
[0025] Figure 3 Scanning electron microscope images, including: (a), (b) S, V-Ni2P / NF; (c), (d) V-Ni2P / NF; (e), (f) S-Ni2P / NF.
[0026] Figure 4 (a) is the total spectrum of each sample.
[0027] Figure 4 (b)-(f) are the XPS spectra of Ni 2p, V 2p, S2p, P 2p, and O 1s of each sample, respectively.
[0028] Figure 5 LSV curves of S, V-Ni2P / NF at different S doping contents, where: (a) HER; (b) OER.
[0029] Figure 6 The OER performance of each sample, including: (a) LSV curve; (b) corresponding Tafel plot; (c) Nyquist plot; (d) C dl ; (e) S, polarization curves of V-Ni2P / NF before and after 5000 CV cycles; (f) chronopotentiometry curves of S, V-Ni2P / NF for 200 hours.
[0030] Figure 7 CV curves at different scan rates during the OER process, including: (a) S, V-Ni2P / NF; (b) S-Ni2P / NF; (c) V-Ni2P / NF; (d) Ni2P / NF.
[0031] Figure 8 HER performance of each sample, including: (a) LSV curve; (b) corresponding Tafel diagram; (c) Nyquist diagram; (d) Cdl; (e) S, polarization curves of V-Ni2P / NF before and after 5000 CV cycles; (f) chronopotentiometry curves of S, V-Ni2P / NF for 200 hours.
[0032] Fig. 9 CV curves at different scan rates during the HER process, including: (a) S, V-Ni2P / NF; (b) S-Ni2P / NF, (c) V-Ni2P / NF; (d) Ni2P / NF.
[0033] Fig.10(a) shows the polarization curves of S, V-Ni2P / NF||S, V-Ni2P / NF in 1M KOH and 1M KOH+0.5MNaCl.
[0034] Fig.10 (b) is the chronopotentiometry curve of S, V-Ni2P / NF in 1 M KOH.
[0035] Fig.10 (c) shows the continuous multi-step chronoamperometric step curves of S, V-Ni2P / NF||S, V-Ni2P / NF in 1M KOH+0.5M NaCl. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The experimental drugs used in the present invention are shown in Table 1, the experimental instruments used are shown in Table 2, and the material characterization instruments used are shown in Table 3.
[0038] Table 1 Main experimental reagents and gases
[0039]
[0040] Table 2 Experimental instruments
[0041]
[0042] Table 3 Instruments and models required for material characterization
[0043]
[0044] Example 1
[0045] A method for preparing a S, V-co-doped porous Ni2P material comprises the following steps:
[0046] (1) Weigh 2.85 mmol Ni(NO3)2·6H2O, 0.15 mmol VCl3, 6 mmol urea and 4 mmol NH4F, dissolve them in 20 mL water and stir for 30 min to obtain a mixed solution;
[0047] (2) Place nickel foam (size 1×2 cm 2 ) and the mixed solution were added into a stainless steel autoclave lined with polytetrafluoroethylene, heated at 120°C for 6 hours, and then rinsed with water and dried to obtain a NiV-LDH precursor;
[0048] (3) NiV-LDH precursor, 0.005 g S powder and 0.5 g NaH2PO2 powder were placed in the downstream, midstream and upstream of the tube of a tubular furnace, respectively. The tube furnace was heated to 350°C at a rate of 2°C / min in argon, then kept warm for 2 h and naturally cooled to room temperature to obtain S, V-Ni2P / NF material.
[0049] Comparative Example 1
[0050] The difference from Example 1 is that VCl3 is not added in step (1). The rest is the same. S-Ni2P / NF is obtained.
[0051] Comparative Example 2
[0052] The difference from Example 1 is that S powder is not added in step (3). The rest is the same. V-Ni2P / NF is obtained.
[0053] Comparative Example 3
[0054] The difference from Example 1 is that VCl3 is not added in step (1) and S powder is not added in step (3). The rest is the same. Ni2P / NF is obtained.
[0055] Experiment 1 Characterization Experiment
[0056] Figure 1 The schematic diagram of the synthesis of S, V-Ni2P / NF. First, NiV-LDH precursor was prepared by a simple hydrothermal method, and then S, V-Ni2P / NF electrode with flower ball structure was prepared by low temperature sulfurization under the protection of flowing Ar gas.
[0057] The prepared samples were characterized by scanning electron microscopy (SEM) and X-ray powder diffractometer (XRD). Figure 2 As shown in the XRD pattern in a, it can be seen that NiV-LDH / NF was successfully prepared on the surface of nickel foam. Except for the two strong peaks assigned to NF (PDF#04-0850), all peaks can be corresponding to the diffraction peaks of Ni(OH)2 (PDF#01-073-6992), and no trace amount of V was detected. The corresponding SEM spectrum ( Figure 2 b) It can be seen that its morphology is a nanoflower-like microsphere composed of many crossed nanosheets, with an average diameter of about 5 μm. Such morphological characteristics indicate that the sample has a large specific surface area. Figure 2As can be seen from Figure c, the doping of S and V does not affect the phase of the material, but only affects the crystallinity of the material. The prepared S,V-Ni2P / NF can match the peak of Ni2P (PDF#65-3544) very well. The diffraction peaks of 2θ at 30.4°, 31.8°, 35.4°, 40.6°, 44.6°, 47.4°, 54.2°, 54.4°, 55.1°, 74.7° and 74.9° correspond to the (110), (011), (200), (111), (021), (210), (300), (002), (211), (400) and (212) planes of Ni2P, respectively. In addition, the doping of S and V causes the peak position to shift, indicating that the doping causes lattice distortion. After the precursor is further phosphated, its morphology is shown in the figure below. Figure 2 As shown in Figure d, the overall morphology inherits the micron flower ball shape of the precursor. The difference is that after S, V-Ni2P / NF is added with sulfur powder for phosphating, the originally smooth nanosheets become rough and many holes appear on them. A large number of open holes can promote the adsorption of reactants to the inner surface of the catalyst material, shorten the transfer distance, improve the reaction efficiency, and will be beneficial to the electrocatalytic performance. In order to explore the effect of S, V doping on the catalyst morphology, S-Ni2P / NF and V-Ni2P / NF samples were also prepared. Figure 3 As shown in a and b, there are a lot of voids on the S, V-Ni2P / NF nanosheets, and the nanosheets are relatively thin, while there are no large number of voids on the Ni2P nanosheets doped only with V ( Figure 3 c, d), indicating that the role of S is to etch the nanosheets, making them thin and porous; Ni2P with only S can be seen from the figure ( Figure 3 e, f), the micron flower ball has a slight collapse, and the nanosheet is composed of small particles and is very rough, indicating that the presence of V can make the nanosheet more rigid and the morphology structure is not easy to collapse. Figure 2 From the element mapping of e and f, it can be seen that S and V are evenly distributed and exist in the form of doping (Table 4), Ni:P is close to 2:1, and Ni2P is the main phase, which is consistent with the results of XRD.
[0058] Table 4 X-ray spectrum data of NFF(V, Na)-P
[0059]
[0060] Figure 4 The X-ray photoelectron spectroscopy (XPS) test results are shown to determine the chemical composition of S, V-Ni2P / NF, S-Ni2P / NF, V-Ni2P / NF, Ni2P / NF samples and the valence changes of elements before and after S and V doping. Figure 4a is the XPS total spectrum of the elements, and the spectrum confirms the presence of Ni, V, S, P, C and O elements in S, V-Ni2P / NF. Figure 4 In the high-resolution photoelectron spectrum of Ni in S, V-Ni2P / NF in b, the peaks at 853.2 and 870.5 eV are attributed to the Ni-P bonds in the material; the diffraction peaks at 856.7, 874.6 eV and 858, 875.3 eV correspond to Ni 2p 3 / 2 and Ni 2p 1 / 2 , indicating the presence of Ni 2+ and Ni 3+ , which is consistent with the reported results. In addition, the diffraction peaks at 862.6 and 879.9 eV are attributed to satellite peaks (named "Sat"). Compared with the undoped Ni2P / NF, the peak position of the double-doped Ni2P / NF in S, V-Ni2P / NF moves toward the lower binding energy, indicating that the synergistic effect of S and V causes the electrons to accumulate around the Ni atoms. Figure 4 c is the high-resolution V 2p spectrum. It can be seen from the figure that the V 2p spectrum is separated into V 2p due to spin-orbit splitting. 3 / 2 and V 2p 1 / 2 The peaks at 516.1 and 523.2, 517.0 and 524.5, 517.95 and 525.6 eV are attributed to V 3+ 、V 4+ and V 5+ Among them, the high-valent V ion is because the electronegativity of S is strong, which increases the valence of V. 4+ The ions are hydrophilic because of their high positive charge and unfilled d orbitals, which can promote the dissociation of water molecules and accelerate the subsequent HER process. Figure 4 d), the diffraction peaks at 162.0eV and 162.9eV belong to S 2- S2p 3 / 2 and S2p 1 / 2 Compared with the undoped S-doped V-Ni2P / NF, the S2p 3 / 2 and S2p 1 / 2 The peak positions all show a negative shift, indicating that the S dopant attracts electrons from V. The MP bond of phosphide and the PO bond of phosphate / phosphite ( Figure 4 e) The P2p peaks appear at 134.1, 129.1 eV and 130.1 eV, respectively, where the PO bonds are formed due to oxidation of the metal phosphide surface when exposed to air. Figure 4f is the O1s spectrum, and it can be observed that the peak at a binding energy of 531.6 eV is attributed to the surface adsorbed water, while the peak at 533.1 is attributed to the PO bond in the phosphate. In XPS, the binding energy is related to the electron transition of the core atomic orbital. Due to different chemical environments, the resulting binding energy will vary slightly. The above results indicate that S, V-Ni2P / NF was successfully synthesized.
[0061] Experiment 2: Electrochemical performance experiment
[0062] Electrochemical tests were performed in a conventional three-electrode system using an electrochemical workstation (CHI660E). The synthesized self-supporting electrode was used as the working electrode, graphite rod and Ag / AgCl were used as the counter electrode and reference electrode, and two different solutions were used as electrolytes, including alkaline fresh water (1MKOH, pH=13.6) and simulated alkaline salt water (1MKOH+0.5MNaCl). The conversion formula between Hg / HgO electrode and standard hydrogen electrode is: E(RHE)=E(Hg / HgO)+0.098+0.059pH. All data were not iR compensated. The electrochemical performance evaluation indicators include:
[0063] (1) Linear sweep voltammetry (LSV)
[0064] The test scan rate is 5mV·s -1 The polarization curve at this time is used to analyze the open circuit potential and overpotential of the catalyst of current and voltage. The smaller the overpotential, the higher the catalytic activity.
[0065] (2) Cyclic voltammetry (CV)
[0066] The test scan rates are 20, 40, 60, 80, and 100 mV·s -1 The electrochemical active surface area (ECSA) of the electrocatalyst was evaluated by calculating the double layer capacitance of the catalyst in the non-Faraday region from the CV curves.
[0067] (3) Electrochemical impedance spectroscopy (EIS)
[0068] The frequency range of EIS test is 0.01 to 10 5 Hz, AC amplitude is 5mV. Evaluate the speed of catalyst reaction kinetics. EIS test potential is 10mA·cm -2 The corresponding potential.
[0069] (4) Stability test
[0070] Through CV testing, the changes in the LSV curve before and after the cycle are observed. The smaller the change, the better the stability. Through chronopotentiometry, the changes in potential during long-term testing at a fixed current are observed. The smaller the change, the better the durability. In addition, a multi-step chronocurrent step test can be used to compare the degree of change in potential during the rise and fall of different currents. If it is symmetrical, it indicates a good mass transfer process.
[0071] The results are as follows:
[0072] In a conventional three-electrode system, the prepared electrode was tested for electrocatalytic activity of OER and HER in 1.0 M KOH. The scan rate of the polarization curve was 5 mV·s -1 All data are not iR corrected. In order to obtain the catalyst with the best S-doping performance, different S-doping contents were adjusted, such as Figure 5 As shown in the figure, when the amount of S powder is 0.005g, the OER and HER performance of S, V-Ni2P / NF is optimal. In 1M KOH electrolyte, the OER performance of the material was tested using a three-electrode system. Figure 6 It can be seen that by comparing a series of catalysts such as S, V-Ni2P / NF, S-Ni2P / NF, and V-Ni2P / NF, the effect of doping on the OER performance of the catalyst is explored. When the V content is 0.2mmol and the S content is 0.005g, the OER performance is the best.
[0073] When the current density is 100 mA cm -2 , its overpotential is 236.4mV, which is better than S-Ni2P / NF (303.4mV), V-Ni2P / NF (379.4mV), Ni2P / NF (306.4mV) and RuO2 / NF (355.4mV). At this time, no Cl - The oxidation reaction of ClER is not possible because the potential difference between ClER and OER is about 480mV in the electrolyte solution with pH>7.46, and the overpotential at this time is only 236.4mV, so ClER reaction will not occur. This shows that the firm micron flower ball structure with holes formed by S and V doped Ni2P is conducive to the infiltration of electrolyte. In addition, in order to study the reaction kinetics mechanism of OER, the Tafel slope can be obtained from the OER polarization curve. Figure 6 b shows that the Tafel slope of S, V-Ni2P / NF is 30.4 mVdec -1 , which is smaller than the Tafel slopes of S-Ni2P / NF, V-Ni2P / NF, Ni2P / NF and RuO2 / NF (38.4, 71.5, 62.1 and 57.4 mV·dec, respectively). -1). This indicates that S, V-Ni2P / NF has the fastest reaction kinetics under alkaline conditions. In addition, the Nyquist curve is also used to study the reaction kinetics, and the diameter of the arc represents the electron transfer resistance. Figure 6 As shown in c, the charge transfer impedance (Rct) of S, V-Ni2P / NF (8.06Ω) is significantly smaller than that of S-Ni2P / NF, V-Ni2P / NF and Ni2P / NF, indicating that S, V-Ni2P / NF has good conductivity and fast electron transfer kinetics. The electrochemical double layer capacitance is linearly related to the electrochemical active surface area. Therefore, the cyclic voltammetry curves at different scan rates ( Figure 7 ) measured the electrochemical double layer capacitance (C dl ) to evaluate the electrochemically active surface area (ECSA). Figure 6 As shown in d, the S,V-Ni2P / NF catalyst with porous micro-flower-like structure shows the largest C dl Value, about 48.5mF·cm -2 , which is significantly higher than that of S-Ni2P / NF, V-Ni2P / NF and Ni2P / NF (26.7, 18.8 and 17.0 mF·cm -2 ), indicating that the S,V-Ni2P / NF with porous micron flower-like structure can provide a larger electrochemical surface area and active sites, thus greatly improving the OER performance. In general, electrocatalytic stability and sustainability are other important parameters for evaluating electrode performance. Figure 6 As shown in e, the LSV polarization curve of S,V-Ni2P / NF after 5000 CV cycles is almost completely consistent with the initial curve. In addition, the long-term chronopotentiometry test is also very stable, as shown in Figure 6 As shown in Figure f, after testing for 200 hours, the voltage holding rate remains close to 92.3%.
[0074] S, V-Ni2P / NF electrode also has good HER catalytic activity and stability. In order to compare the performance, samples including S, V-Ni2P / NF, S-Ni2P / NF, V-Ni2P / NF, Ni2P / NF and Pt / C / NF were also tested under the same conditions. HER polarization curves are shown in Figure 2. Figure 8 a. The S, V-Ni2P / NF composite catalyst exhibits excellent electrocatalytic activity at 100 mA·cm -2 It has a low overpotential of 259.6 mV at the HER current density, which is slightly higher than Pt / C / NF (355.4 mV) and much lower than S-Ni2P / NF (286.6 mV), V-Ni2P / NF (384.6 mV) and Ni2P / NF (550.6 mV). Figure 8b is the Tafel slope of all samples, S, V-Ni2P / NF is only 91.2 mV·dec -1 , compared with S-Ni2P / NF (115.8mV·dec -1 )、V-Ni2P / NF(120.7mV·dec -1 ) and Ni2P / NF (127.5mV·dec -1 ) is smaller than that of Pt / C / NF (48.9mV·dec -1 The electrode kinetics of the electrocatalysts were further analyzed by electrochemical impedance spectroscopy (EIS). Figure 8 As can be seen in c, the interface reaction resistance results obtained by simulating the circuit are as follows: the charge transfer impedance of S, V-Ni2P / NF (12.6Ω) is significantly smaller than that of S-Ni2P / NF (14.8Ω), V-Ni2P / NF (16.9Ω) and Ni2P / NF (72.9Ω). EIS results show that anion-cation co-doped Ni2P / NF can effectively reduce the impedance during electron transfer, thereby enabling S, V-Ni2P / NF to achieve rapid electron transfer and high conductivity. At the same time, through CV ( Fig. 9 ) measured and obtained C dl , in order to further explore the source of the high electrocatalytic activity of S,V-Ni2P / NF. Figure 8 d shows the C of S, V-Ni2P / NF dl 57.5mFcm -2 , higher than S-Ni2P / NF (49.9mF·cm -2 )、V-Ni2P / NF(21.9mF·cm -2 ) and Ni2P / NF (4.4mF·cm -2 ). The high electrochemically active surface area (ECSA) means that S,V-Ni2P / NF exposes more active sites due to the composite structure, which provides more catalytic active centers during the reaction. Figure 8 It can be seen from the figure that the overpotential of S, V-Ni2P / NF does not change significantly after 5000 CV cycles. -2 After 200h of durability test, the voltage retention rate remained at 93.5%, showing excellent stability and durability.
[0075] Based on the excellent electrocatalytic activity of S, V-Ni2P / NF in HER and OER, S, V-Ni2P / NF can be used as anode and cathode in a two-electrode system for full water splitting test. Fig.10In a, in 1.0M KOH + 0.5M NaCl, S, V-N2P / NF||S, V-Ni2P / NF only need 1.48 and 1.72 V to reach 10 mA cm -2 and 100mA·cm -2 In addition, if Fig.10 As shown in b, in 1.0MKOH, S, V-Ni2P / NF can be continuously tested for more than 150h, and after the stability test, the voltage retention rate is still 94.3%; In addition, the performance of S, V-Ni2P / NF was studied by continuous multi-step current step test, such as Fig.10 As shown in Figure c, the sample has good mass transfer process and stability. The main reason for its excellence is that the micron flower ball composed of nanosheets has a porous structure, which is conducive to the transmission of electrolyte and the discharge of gas, exposing active sites, and the interaction between S and V.
[0076] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the scheme disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0077] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a S, V-co-doped porous Ni2P material, characterized in that: The following steps are involved: (1) Weigh Ni(NO3)2·6H2O, VCl3, urea and NH4F, dissolve them in water, and stir to obtain a mixed solution; (2) adding the nickel foam and the mixed solution into a stainless steel autoclave lined with polytetrafluoroethylene, heating to react, and then washing with water and drying to obtain a NiV-LDH precursor; (3) NiV-LDH precursor, S powder and NaH2PO2 powder are placed in the downstream, midstream and upstream of the tube of a tube furnace, respectively, the tube furnace is heated in argon gas, then kept warm and naturally cooled to room temperature to obtain S, V-Ni2P / NF material.
2. The method for preparing a S, V-co-doped porous Ni2P material according to claim 1, characterized in that: The molar ratio of Ni(NO3)2·6H2O, VCl3, urea and NH4F in step (1) is 2.85:0.15:6:
4.
3. The method for preparing a S, V-co-doped porous Ni2P material according to claim 1, characterized in that: The stirring time in step (1) is 30 min.
4. The method for preparing a S, V-co-doped porous Ni2P material according to claim 1, characterized in that: The heating temperature in step (2) is 120° C. and the heating time is 6 hours.
5. The method for preparing a S, V-co-doped porous Ni2P material according to claim 1, characterized in that: The mass ratio of S powder to NaH2PO2 powder in step (3) is 1:
100.
6. The method for preparing a S, V-co-doped porous Ni2P material according to claim 1, characterized in that: The heating rate of the tubular furnace in step (3) is 2°C / min, the temperature is raised to 350°C, and the holding time is 2h.
7. A S, V-co-doped porous Ni2P material prepared according to the method according to any one of claims 1 to 6.
8. Use of the S, V-co-doped porous Ni2P material according to claim 7 in salt water decomposition.
Citation Information
Patent Citations
Preparation method of sulfur-doped nickel phosphide nano powder and application in electrolysis of water
CN110215928A
Vanadium-doped nickel phosphide material with spherical micron-flower-shaped structure as well as preparation method and application of vanadium-doped nickel phosphide material
CN117263149A